PENGARUH PROGRAM MARKETING COMMUNICATION TERHADAP KEPUTUSAN BERKUNJUNG DI TAMAN NASIONAL UJUNG KULON (Survei pada Wisatawan yang Berkunjung ke Taman Nasional Ujung Kulon) - Nurjanah, Novarin; Waluya, Bagja (Universitas Pendidikan Indonesia, 2012)
Banten is one province in Indonesia which has a variety of objects and the potential tourism. One of the tourist area is Ujung Kulon National Park. Ujung Kulon National Park is a kind of ecological tourism (ecotourism) that located in Pandeglang. This national park is very well known to foreign tourists and domestic tourists, primarily as a place of preservation of the Javan rhino (one-horned rhino and buffalo). However, tourist arrivals Ujung Kulon National Park in 2010 has decreased, therefore necessary to conduct research on aspects related to increasing the number of visits. including through programs conducted by the marketing communication manager Ujung Kulon National Park. Based on this, the researcher interested to conduct research The Influence of Marketing Communication Programs towards Visiting Decision in Ujung Kulon National Park. The problem of this study are 1). How the idea of marketing communication programs, 2). How the idea of the decision to visit, 3). How does influence marketing communication programs to the visiting decision. This study aims to obtain marketing communication description, visiting decision description and the influence of marketing communications programs to the visiting decision. The technical analysis of the data in this study is used the analysis of the path (path analysis) with a sampling technique is systematic random sampling of 100 respondents. The results of this study indicate that marketing communication programs have a significant influence on the decision to visit. Greatest effect is obtained through advertising and the smallest effect is obtained through the event and experience. This is because advertising is a means of promotion through various media such as print and electronic media that can provide more information to tourists. Suggestion for managers Ujung Kulon National Park, should further develop marketing programs through organized events and improve the quality of tourist attractions as well as provide information best time to visit the National Park Ujung Kulon.